The civic virtue of philotimia: rhetoric, ideology, and politics in democratic Athens - Aloumpi, M (2018)
This thesis explores the place that philotimia held in the value system and ideology of democratic Athens in the period between 430 and 320 BCE by examining the rhetoric of philotimia in instances of public speech, especially in the courtrooms and the Assembly. Chapter 1 explores the relation between philotimia and metriotēs in courtroom rhetoric of Demosthenes’ time. Section 1 shows that being philotimos and being metrios could be presented as belonging to the same mentality, that of prioritizing public interest without ignoring appropriate personal ambitions and goals. Section 2 takes Against Meidias as a case study. In the rhetoric of Against Meidias, we find an account of what it means to be an exemplary elite philotimos citizens and what it means to be a rich hybristēs in democratic Athens. Chapter 2 starts off by showing that the idea of civic-oriented philotimia that we find in Against Meidias is systematically found in courtroom speeches and honorific inscriptions from the mid-fourth century onwards. Section 2 moves backwards in time and explores the rhetoric of philotimia in the time of Lysias. In the last years of the fifth century and beginning of the fourth, I identify a greater need to warn the dikasts against bad or dangerous philotimoi rather than present oneself as a good philotimos. At the same time, the rhetoric of civicoriented philotimia can be traced as far back as 403/402, which indicates that it was not a novelty of the mid-fourth century. Section 3 explores cases of philotimoi that took action outside the democratic city as depicted in the speeches of Lysias and Demosthenes. Chapter 3 explores the rhetoric of philotimia in political discussions. The rhetoric of philotimia is very limited when a speaker is discussing his contributions to policy-making, either directly in the Assembly or when discussions of politics are transferred in the courtroom. Section 1 discusses assembly scenes in Thucydides and Aristophanes. Section 2 focuses on representations of political competition in the time of Demosthenes. Section 3 discusses the rhetoric of charis in the deliberative speeches of Demosthenes. Section 4 explores Demosthenes’ self-presentation and collective philotimia in his trial battles with Aeschines. This study does not argue for a semantic shift in the meaning of philotimia from a negative into a positive value, but shows that philotimia was an ambivalent concept throughout the period examined. The closely regulated and selective promotion of philotimia that is evidenced in the rhetoric of the courtroom and the Assembly reflects the duality of philotimia as a concept and the fact that the Athenians were very much alert to it.